Correlação entre sintomas vocais e suas possíveis causas em um grupo de coralistas da cidade de São Paulo - Gonçalves, Tatiana de Abreu Castro (2007)
Introduction: In the field of Speech Therapy, there are few epidemiologic researches, especially those which investigate issues related to the singing voice. Aim: This study related a choral group s vocal symptoms and their probable causes, according to gender and vocal classification. Methods: The subjects of this study were 143 choral singers (58,7% female and 41,3% male) from a University in the City of São Paulo. Subjects age varied between 18 and 45 years, and subjects had different vocal classifications. The participants answered a questionnaire that was adapted from the one proposed by GUERRA (2005), which included, questions which enabled the characterization of the group, questions that evaluated the presence of vocal symptoms, and their likely causes, in the singers opinions. The data was analyzed considering numeric values and percentage, of the following: most frequent vocal symptoms and related causes according to gender (male x female); most frequent symptoms and related causes in sopranos and altos; most frequent symptoms and related causes in tenors and bases; overall symptoms and their related causes; and most frequent symptoms in spoken voice, singing voice, and both. In order to perform the statistical analysis, the SPSS (Statistical Package for Social Sciences) version 13.0 was used, and the level of significance was established at 5% (0.050). In addition, the Mann- Whitney; Test was used to analyze possible differences between gender and vocal classification, and Spearman s correlation test was used to verify the relationship between vocal symptoms and their possible causes. Results: From the subjects amongst the male gender, 25% did not mention any of the listed symptoms, as well as 22.9% of the female subjects did not mention any of the above mentioned symptoms. The symptoms that were most mentioned were phlegm/secretion, (44,6%, both for male and female), followed by hoarseness (22,9% for female and 26,8% for male) and dry cough (20,5% for female and 14.3% for male). When comparing gender, there was significant difference (p=0,015) in favor of male subjects, with regards to weak voice. With regards to vocal classification, dry throat and dry mouth, differentiate altos and sopranos. Amongst the causes, that were most mentioned by the group, as those which could possibly explain the occurrence of the referred symptoms, were: flu (50,8%), intense use of the singing voice (42,4%) and allergies (41,6%). Conclusions: The vocal symptoms which were most frequently mentioned were phlegm/secretion, hoarseness and wet cough. Hoarseness was the symptom most mentioned in spoken voice, while phlegm/secretion was the most common in singing voice, or both. When corelating with gender, the symptom of weak voice was present in favor of male subjects, and when co-relating vocal classification, the symptoms of dry throat and dry mouth were most common amongst the altos. The subjects showed previous knowledge when relating symptoms to possible causes. Amongst these, the most commonly mentioned were flu, intensive voice usage and allergy. Intense singing and spoken voice usage, respiratory infections, allergies and digestive issues were specifically related to hoarseness